ナンキョク イキ 15次 デ サイシュウ シタ ドウブツ ヒョウホン ノ ガイヨウ 1 - 星野, 孝治; ホシノ, タカハル; HOSHINO, Takaharu (国立極地研究所, 1976)
P(論文) 第15次隊海洋生物隊員として採集してきた動物標本の概要の一部を報告する.これらは,1.オングル島,ラングホブデ沿岸での採集物,2.西オングル島で採集した動物化石標本,3.「ふじ」船上から採集したプランクトン類である. The zoological collections obtained from the Antarctic in the 15th Japanese Antarctic Research Expedition are summarized in this paper. They are 1. collections from the coast of Ongul Islands and Langhovde, 2. fossil animals from West Ongul Island, 3. a part of plankton collection obtained aboard the FUJI. The number of specimens, a brief morphological note, etc., of each collection are given. departmental bulletin paper